Excessive Daytime Sleepiness and Injury of the Ascending Reticular Activating System Following Whiplash Injury - Jang, Sung H.; Kim, Seong H.; Kwon, Young H. (Frontiers in Neuroscience, 2018)
Objectives: This study investigated injuries of the ascending reticular activating system (ARAS) following whiplash injury, in patients with excessive daytime sleepiness (EDS). Methods: Twenty-three patients with whiplash injury and 26 healthy control subjects were recruited for this study. Epworth Sleepiness Scale (ESS) was used for evaluating sleepiness. According to the ESS score, the patients were classified into two groups: subgroup A – ESS score <10, and subgroup B – ESS score ≥10. Three components of the ARAS (lower dorsal, lower ventral, and upper) were evaluated for fractional anisotropy (FA) and tract volume (TV). Results: No significant differences were observed in the FA and TV values of the lower dorsal and upper ARAS between the patient and control groups (p > 0.05). Conversely, the values of FA and TV in the lower ventral ARAS of the patient group were significantly lower than those of the control group (p < 0.05). Comparing the values of subgroups A and B, the TV value of subgroup B was significantly lower than subgroup A (p < 0.05). However, no significant differences were observed in the values of the FA and TV in the lower dorsal and upper ARAS, and the FA value in the lower ventral ARAS (p > 0.05). Conclusions: We found significant injury of the lower ventral ARAS in EDS patients with whiplash injury. These results suggest that diffusion tensor tractography (DTT) could provide useful information for detecting injuries of the ARAS following whiplash injury, in patients with EDS.